Conflict Resolution on Violence Behavior in Yogyakarta (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The study aims to analyze conflict resolution on domestic violence behavior (KDRT) in Yogyakarta. The study results stated that the presence of domestic violence cases in Yogyakarta was considered small with the comparison of the population in the area. Meanwhile, the case of domestic violence in Yogyakarta was caused by factors such as stress due to domicile in the Metropolitan City; work environment; economy, and other factors. In order to take preventive measures against domestic violence behavior, mediation is needed. The concept of Islamic mediation in Indonesia is authorized by Badan Penasihat, Pembinaan, dan Pelestarian Rumah Tangga (the Household Advisory, Guidance, and Preservation Agency) or BP4. BP4 can mediate ongoing cases with spouses that impact domestic violence behavior. Meanwhile, the anticipation of harmful impacts on children as victims of domestic violence can be done through interpersonal communication; namely, the closest family communicates intensely with children through three steps; firstly, provide physical and mental strengthening; secondly, accompanying children as long as the domestic violence case has not been completed; thirdly, strengthen the spiritual side of the child. Such an effort is one of the anthropological and sociological resolutions of domestic violence conflicts